The Potential of Omega-3 Fatty Acids in the Treatment of Dry Eye Disease: A Narrative Review - Nejra Hodžić; Ines Banjari; Priyadarshini Bhoi; Zumra Hodžić; Zlatko Mušanović; Amra Nadarević-Vodenčarević (Al-Anbar Medical Journal)
As one of the most common diseases in ophthalmology today, dry eye disease (DED) poses a great challenge for public health systems globally. This is a multifactorial condition involving the production/evaporation of tears and consequential damage to the ocular surface. Symptoms of DED like discomfort and visual disturbance alter a person’s quality of life and pose a significant economic burden to healthcare systems. Today’s lifestyle favors DED development, especially long-term exposure to screens, poor sleep quality, and a diet abundant in saturated fats and omega-6 fatty acids, and we can expect that its prevalence will extend far beyond the currently estimated 10%. The underlying inflammation and symptoms of DED, are treated with various anti-inflammatory agents and autologous and/or allogeneic serum drops. Considering the role of lifestyle in DED pathophysiology, lifestyle modifications, including diet, sleep, and physical activity are getting more attention. Among them, supplementation with omega-3 fatty acids shows the most promising results in alleviating subjective and objective measures of DED through a direct effect on the stability and production of the tear film, inflammation markers, and corneal nerve regeneration. We aimed to provide insights into currently available research findings supporting omega-3 fatty acids as a valuable adjuvant therapy in treating DED.